2015
DOI: 10.1186/s13046-015-0164-3
|View full text |Cite
|
Sign up to set email alerts
|

Decreased expression of ARID1A associates with poor prognosis and promotes metastases of hepatocellular carcinoma

Abstract: BackgroundHepatocellular carcinoma (HCC) is a common malignancy worldwide, which is especially prevalent in Asia. Elucidating the molecular basis of HCC is crucial to develop targeted diagnostic tools and novel therapies. Recent studies have identified AT-rich interactive domain-containing protein 1A (ARID1A) as a broad-spectrum tumor suppressor. We evaluated the clinical implications of decreased ARID1A expression in HCC, and investigated the mechanisms of ARID1A-mediated tumor suppression.MethodsQuantitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
69
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(83 citation statements)
references
References 34 publications
(39 reference statements)
12
69
0
Order By: Relevance
“…The fact that Arid1a heterozygosity promoted metastasis is consistent with previous studies that showed partial ARID1A loss in human gastric and liver cancer samples was associated with metastasis and that incomplete ARID1A knockdown in cancer cell lines promoted migration and invasion (He et al, 2015; Huang et al, 2012; Yan et al, 2014). While we provided in vivo evidence that this also occurred in genetically engineered mouse models and offered mechanisms by which this occurs, it is likely that the downregulation of many metastasis or growth suppressing genes collectively contribute to the phenotypic effects of ARID1A loss in tumors, and our study identified only a subset of such genes.…”
Section: Discussionsupporting
confidence: 91%
“…The fact that Arid1a heterozygosity promoted metastasis is consistent with previous studies that showed partial ARID1A loss in human gastric and liver cancer samples was associated with metastasis and that incomplete ARID1A knockdown in cancer cell lines promoted migration and invasion (He et al, 2015; Huang et al, 2012; Yan et al, 2014). While we provided in vivo evidence that this also occurred in genetically engineered mouse models and offered mechanisms by which this occurs, it is likely that the downregulation of many metastasis or growth suppressing genes collectively contribute to the phenotypic effects of ARID1A loss in tumors, and our study identified only a subset of such genes.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have demonstrated that decreased expression of ARID1A, which encodes another protein of the ARID family, enhances gastric cancer cell or HCC cell migration via transcriptional silencing of E-cadherin [25, 26]. Moreover, the BRG-1 subunit of the SWI/SNF complex has been reported to regulate CD44 expression and play a critical role in regulating cellular adhesion and metastasis [27, 28].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that downregulation of ARID1A, which encodes another ARID protein of the SWI/SNF family, promotes gastric cancer cells or HCC cell migration by repression of epithelial marker E‐cadherin . Thus, we further explored the effects of ARID2 on E‐cadherin expression and cell migration in stable HBx‐expressing cell lines.…”
Section: Resultsmentioning
confidence: 98%
“…Previous studies have reported that downregulation of ARID1A, which encodes another ARID protein of the SWI/SNF family, promotes gastric cancer cells or HCC cell migration by repression of epithelial marker E-cadherin. (27,28) Thus, we further explored the effects of ARID2 on E-cadherin expression and cell migration in stable HBx-expressing cell lines. Transwell assays demonstrated that ARID2 significantly inhibited cell migration and enhanced the expression of the epithelial marker E-cadherin in SK-HBx and Huh7-HBx cell lines (Fig.…”
Section: Resultsmentioning
confidence: 99%